Performance analysis of the coherent FMCW photonic radar system under the influence of solar noise - Kumari, Annapurna; Kumar, Amitesh; Reddy, Gurijala Sai Tejesh (Frontiers in Physics, 2023)
The real-time high-resolution target detection in radar applications has increased the demand for photonic radar systems due to their higher bandwidth and faster processing capabilities over conventional microwave radar. Additionally, photonic-based radar technology can revolutionize the limited performance of conventional microwave radar caused by various atmospheric attenuations. This article presents a frequency-modulated continuous wave photonic radar system using coherent detection. The performance of the proposed system is theoretically investigated under the effect of various real-time atmospheric weather attenuations and the influence of solar background noise which is further verified on the simulation platform. This study is conducted for different atmospheric weather conditions such as clear, haze, and fog to highlight the practical limitation of free space links in the presence of solar background noise. The detected signal at different target ranges with and without solar noise is measured and then compared in terms of signal-to-noise ratio. Furthermore, the impact of solar noise on the system performance when the sun is at different sky conditions and zenithal angles is also analyzed. The results presented here provide insight into designing photonic radar systems for practical applications like autonomous vehicle radar systems, self-traffic control, and navigation.